Pengaruh Kualitas Produk dan Brand Image Terhadap Keputusan Pembelian Sepeda Roadbike Pada Konsumen Toko Bike Republic Medan - Billy Hafiz Yazid; Ihsan Effendi; Syafrida Hafni Sahir (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the effect of product quality and brand image on purchasing decisions of road bike consumers at Bike Republic Store Medan. This research uses a quantitative approach with a causal associative method. The research data were obtained through the distribution of questionnaires to 90 respondents who were consumers of Bike Republic Store Medan using a purposive sampling technique. The data analysis method used is multiple linear regression analysis with classical assumption tests, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination. The results show that partially product quality has a positive and significant effect on purchasing decisions with a t-count value of 2.989 which is greater than the t-table value of 1.987 and a significance value of 0.004 < 0.05. Brand image also has a positive and significant effect on purchasing decisions with a t-count value of 4.195 which is greater than the t-table value of 1.987 and a significance value of 0.000 < 0.05. Simultaneously, product quality and brand image have a positive and significant effect on purchasing decisions with an F-count value of 90.223 which is greater than the F-table value of 3.951 and a significance value of 0.000 < 0.05. In addition, the coefficient of determination shows an R Square value of 0.670, which means that product quality and brand image are able to explain purchasing decisions by 67%, while the remaining 33% is influenced by other variables outside this study.